Problematics of the Biological Father’s Status as Guardian for a Child Born from an Extramarital Relationship : A Study at the Office of Religious Affairs of Palu City - Halima Halima; Adam Adam; Ermawati Ermawati (State Islamic University Datokarama Palu, 2026)
This study examines the legal status of a biological father as a marriage guardian (wali nikah) for a child born out of wedlock and analyzes the practice of the Office of Religious Affairs (KUA) of West Palu in determining marriage guardianship. Using a qualitative field research approach, data were collected through interviews, observation, and documentation and analyzed descriptively. The findings show that under Islamic law and the Compilation of Islamic Law, a child born outside a lawful marriage has a legal lineage only with the mother and the mother’s family. Consequently, the biological father is not legally recognized as a valid marriage guardian. In practice, the KUA of West Palu determines that when a child is born less than six months after the marriage of the biological parents, the biological father cannot act as the marriage guardian, and a judicial guardian (wali hakim) must be appointed instead. However, from the perspective of child protection, particularly in light of Maqāṣid al-Sharī‘ah and the decision of the Constitutional Court of Indonesia No. 46/PUU-VIII/2010, there is room for reconsidering the role of biological fathers in protecting the civil rights of children born outside marriage. This study contributes to the discourse on the development of family law and marriage administration in Indonesia.